2004
DOI: 10.1159/000078569
|View full text |Cite
|
Sign up to set email alerts
|

A comparative karyological study of the blue-breasted quail (<i>Coturnix chinensis</i>, Phasianidae) and California quail (<i>Callipepla californica</i>, Odontophoridae)

Abstract: We conducted comparative chromosome painting and chromosome mapping with chicken DNA probes against the blue-breasted quail (Coturnix chinensis, CCH) and California quail (Callipepla californica, CCA), which are classified into the Old World quail and the New World quail, respectively. Each chicken probe of chromosomes 1–9 and Z painted a pair of chromosomes in the blue-breasted quail. In California quail, chicken chromosome 2 probe painted chromosomes 3 and 6, and chicken chromosome 4 probe painted chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
(38 reference statements)
3
19
1
Order By: Relevance
“…The discrepancy between the present data and the earlier reported data (Shibusawa et al, 2001(Shibusawa et al, , 2004aSchmid et al, 2005) can be easily explained. Since the short arm of chicken chromosome 4 represents an ancestral microchromosome (Shibusawa et al, 2002;Guttenbach et al, 2003;Derjusheva et al, 2004;Itoh & Arnold, 2005), precise assignment of chicken 4p molecular markers by FISH to metaphase chromosomes seems to be a bit tricky.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The discrepancy between the present data and the earlier reported data (Shibusawa et al, 2001(Shibusawa et al, , 2004aSchmid et al, 2005) can be easily explained. Since the short arm of chicken chromosome 4 represents an ancestral microchromosome (Shibusawa et al, 2002;Guttenbach et al, 2003;Derjusheva et al, 2004;Itoh & Arnold, 2005), precise assignment of chicken 4p molecular markers by FISH to metaphase chromosomes seems to be a bit tricky.…”
Section: Resultscontrasting
confidence: 99%
“…FISH results showed no rearrangements in quail chromosomes 3 and 5 and conformed with the inversions described earlier on quail chromosomes 1 and 2 as compared to the homologous chicken chromosomes (Shibusawa et al, 2001(Shibusawa et al, , 2004aSchmid et al, 2005). Previous data obtained using FISH to mitotic chromosomes suggested that chicken and quail chromosomes 4 differ by a pericentric inversion.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, comparative chromosome mapping has enabled us to identify intrachromosomal rearrangements, which cannot be detected precisely by chromosome painting. However, comparative chromosome mapping with functional genes and/or cytogenetic DNA markers has been performed for a few avian species (including the California condor, domestic duck, flycatchers, Guinea fowl, Japanese quail, New World quails, turkey, and zebra finch) (Shibusawa et al, 2001(Shibusawa et al, , 2002(Shibusawa et al, , 2004aItoh et al, 2006;Fillon et al, 2007;Stapley et al, 2008;Modi et al, 2009;Skinner et al, 2009;Backström et al, 2010;Zhang et al, 2011). Therefore, a lack of information of intrachromosomal rearrangements between different species makes it difficult to delineate the process of avian karyotype evolution precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-species chromosome hybridization (termed Zoo-FISH) and subsequent comparative gene mapping delineates accurately the chromosomal orthologies between distantly related species and the chromosome rearrangements that have occurred during evolution. Comparative chromosome painting in birds with chicken probes has been performed for over 30 species in at least nine orders (Shetty et al 1999, Schmid et al 2000, Raudsepp et al 2002, Guttenbach et al 2003, Kasai et al 2003, Derjusheva et al 2004, Shibusawa et al 2004a, b, Itoh & Arnold 2005, de Oliveria et al 2005, Nanda et al 2006, reviewed in Griffin et al 2007). …”
Section: Introductionmentioning
confidence: 99%